2011
DOI: 10.1111/j.1399-3062.2011.00650.x
|View full text |Cite
|
Sign up to set email alerts
|

Blood stream infections after allogeneic stem cell transplantation: a single‐center experience with the use of levofloxacin prophylaxis

Abstract: Blood stream infections (BSIs) remain one of the major causes of morbidity and mortality for patients receiving an allogeneic hematopoietic stem cell transplantation (HSCT). In the present study, we evaluated the incidence and characteristics of BSI within 1 year after allogeneic HSCT in 269 consecutive adult patients who received antibacterial prophylaxis with levofloxacin. Cumulative incidence of BSI was 12% (95% confidence interval, 8-16%). Bacteria were responsible for 30 out of the 32 BSI, while fungi wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
30
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 19 publications
13
30
1
2
Order By: Relevance
“…This rate is lower than that noted in other units of our hospital and those in other studies [3,20,27,28]. Busca et al reported that quinolone use may induce the resistance rate against quinolone itself and even against some other antibiotics [28]. However, despite routine use of quinolone prophylaxis, increased rates of resistance have not been observed in patients undergoing prophylaxis.…”
Section: Discussioncontrasting
confidence: 65%
“…This rate is lower than that noted in other units of our hospital and those in other studies [3,20,27,28]. Busca et al reported that quinolone use may induce the resistance rate against quinolone itself and even against some other antibiotics [28]. However, despite routine use of quinolone prophylaxis, increased rates of resistance have not been observed in patients undergoing prophylaxis.…”
Section: Discussioncontrasting
confidence: 65%
“…However, during the study period there was a lower rate of fluoroquinolones resistance amongst bloodstream E. coli hospital isolates (29-38%) and there were few cases of bloodstream infections caused by ESBL-producers E. coli , with resistance to fluoroquinolones in 76.3% of strains [12]. Amongst patients undergoing allogenic transplant and levofloxacin prophylaxis, coagulase-negative staphylococci were the most commonly isolated Gram-positive pathogens and E. coli was the most commonly isolated Gram-negative bacteria [13]. Resistance to fluoroquinolones was 87% amongst Gram-positive isolates and 50% amongst Gram-negative rods.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the emergence of antimicrobial resistance, fluoroquinolone prophylaxis may be considered as an appealing option in recipients of HSCT. However, their usefulness in prophylaxis in allogeneic HSCT should be evaluated in randomized trials (112, 113). …”
Section: Treatment Of S Maltophilia Infectionsmentioning
confidence: 99%